Microstructure and Nanoscale Rock Mechanical Properties of Coal: Applications to CO2 Storage - Zhang, Yihuai (Curtin University, 2017)
In this thesis, the coal microstructure was investigated to better understand the related nanoscale rock-mechanical properties, and morphological changes for different effective stresses and during water and CO2 adsorption, including related porosity and permeability changes. Using in-situ reservoir condition x-ray micro-computed tomography imaging, it was observed for the first time how the micro cleat structure inside the coal matrix closed induced by supercritical CO2 flooding in-situ, and associated fracturing of the mineral phase.